Manganese protoporphyrin IX reconstituted myoglobin capable of epoxidation of the C=C bond with Oxone (R) - Cai, Yuan-Bo; Yao, Si-Yu; Hu, Mo; Liu, Xiaoyun; Zhang, Jun-Long (Inorganic Chemistry Frontiers, 2016)
Replacement of the native heme cofactor by manganese protoporphyrin IX (MnPPIX) to reconstitute manganese myoglobin (Mn(III)Mb) is an important approach to investigate the reactivity of the Mn center inside protein scaffolds. However, unlike the Mn porphyrin synthetic model compounds, MnPPIX reconstituted myoglobins (Mn(III)Mb) have no reactivity in the epoxidation of styrene using H2O2, which was attributed to the low reactivity of the Mn-IV=O intermediate after homocleavage of the O-O bond in manganese peroxide. To address this issue, we herein chose Oxone (R) (2KHSO(5)center dot KHSO4 center dot K2SO4), a well-known oxidant undergoing O-O bond heterocleavage. After screening 7 mutants and wild-type Mn(III)Mb, we found that the L29H/F43H mutant could generate a new species ([Mn-IV=O]+(center dot)), tentatively assigned by using UV-vis and EPR spectra, through heterocleavage of the O-O bond. Computational docking showed hydrogen bonds between three distal histidines (H64, L29H and F43H) and anions, which increase the binding affinity to persulfate. With Oxone (R) as the oxidant, Mn(III)Mb (L29H/F43H) showed the highest reactivity toward the epoxidation of styrene, different from that with the H2O2 oxidant. This work demonstrates the first example of MnPPIX reconstituted Mb which could catalyze styrene epoxidation and provides new insights to further explore the reactivity of the Mn center in protein scaffolds. National Scientific Foundation of China [20971007, 21101169, 21271013, 21571007]; National Key Basic Research Support Foundation of China (NKBRSFC) [2010CB912302, 2015CB856300, 2015CB856301] SCI(E) ARTICLE xiaoyun.liu@pku.edu.cn; zhangjunlong@pku.edu.cn 10 1236-1244 3